Ritual Pethik Pari sebagai Pembentukan Ulang Individualitas Petani : Studi tentang Budaya Pethik Pari di Desa Dukuh Dempok, Wuluhan, Kabupaten Jember - Fitrotin Nisa; Sofia Nabilla Bayani; Adellisa Wardani; Dinda Clarita Salsadillah (Journal Social and Humaniora, 2021)
The Pethik Pari tradition is a tradition of the Javanese farming community. This tradition is in the form of a series of selamatan ritual performed as a form of gratitude of the farmers to God Almighty for abundant sustenance through good harvests. The Pethik Pari ritual used to be carried out by Dukuh Dempok Village farmers individually in their homes by simply carrying out a simple slametan. But now, the ritual procession is changing and carried out jointly by farmers in the fields by carrying out slametan, Wayang’s performances, and fishing together in the rice fields. With the change in the implementation of the ritual procession, making the Pethik Pari ritual a re-establishment of the individuality of peasants in Dukuh Dempok Village. The ritual tradition of Pethik Pari itself, is also a symbol of the Javanese peasant community that there is a belief in the existence of Dewi Sri as a goddess of prosperity. This research uses descriptive qualitative method with a case study approach. Data was collected through in-depth interviews with informants from the head of the farmers' groups and Dukuh Dempok Village farmers. The focus of this study was to determine the re-establishment of the individuality of farmers in Dukuh Dempok village, Wuluhan, Jember, East Java.